PROBING THE THEORY OF SUBJECTIVE DEVELOPMENT IN MULLA SADRA'S EPISTEMOLOGY - Masouleh, Abbas Kharabi; Mamat, Mohd Zufri; Hasbullah, Maisarah (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
Mullā Ṣadrā’s approach to the reality of knowledge to a large extent slopes down to a kind of subjectivism. He viewed the process of obtaining knowledge as an extension of the human soul from existential potential to actuality and from existential deficiency to perfection. Considering his understanding of realism, a question of consonance with his subjectivist inclination requires inquiry. The author applies an interdisciplinary approach in a close examination of Ṣadrā’s epistemology that reveals a kind of subjectivism contained in his epistemic exposition, especially in his emphasis on the existential perfection of the human soul. The effort helps us reconsider the foundations of his pioneering work on transcendent theosophy.